Genistein induces apoptotic cell death associated with inhibition of the NF‐κB pathway in adult T‐cell leukemia cells. (18th April 2013) - Yamasaki, Masao; Mine, Yoshihiro; Nishimura, Misato; Fujita, Satoshi; Sakakibara, Yoichi; Suiko, Masahito; Morishita, Kazuhiro; Nishiyama, Kazuo
Abstract We have shown that genistein inhibits the growth of adult T‐cell leukemia (ATL) cells in vitro and in vivo, and this leads to pronounced G2/M arrest. This report shows that genistein induces apoptotic death in ATL cells. Although the pan‐caspase inhibitor, Z‐VAD‐fmk, did not inhibit genistein‐induced apoptosis, release of apoptosis‐inducing factor (AIF) into the cytosol occurred. Poly‐ADP ribose polymerase inhibition also abrogated genistein‐induced apoptosis. Genistein decreased nuclear p65 translocation and IκBα phosphorylation, and downregulated the anti‐apoptotic proteins, XIAP, cIAP and survivin, NF‐κB‐responsive gene products. Thus, genistein is a promising agent for ATL that induces caspase‐independent apoptosis through inhibition of the NF‐κB pathway.